It came form beneath the sink! - Stine, R. L.; Copyright Paperback Collection (Library of Congress) (New York : Scholastic Inc., 1995)
A practical joke involving two scary pumpkin heads turns into a Halloween night of terror when the pumpkins develop strange hissing voices and flames shoot out of their faces.
"An Apple paperback."
"A Parachute Press book."
G6
Keywords: Halloween -- Fiction; Jack-o-lanterns -- Fiction; Horror tales; Children's stories; Horror fiction